Attitude and perceived barriers towards conducting research among medical professionals - Shrestha, Sailendra Kumar Duwal; Maharjan, Rupak; Pradhan, Amita; Acharya, Sudeep (Journal of Chitwan Medical College, 2021)
Background: Medical research is the foundation for gaining scientific information and learning. However, in developing countries like Nepal, it is given low priority, mostly due to inadequate research funding. This study was aimed to assess the attitude and the barriers associated with medical research. Methods: This descriptive cross-sectional study was conducted among the medical professionals of Nepal from 10th October to 10th November 2021. A self-administered questionnaire was used to collect the data. Collected data included demographics, a questionnaire related to attitude and barriers to research among medical professionals of Nepal. The data was collected, compiled, and analyzed by using Statistical Package of Social Science (SPSS) version 26. The data were analyzed using descriptive statistics. Results: In total 83 participants with a mean age of 32.8±4.7 years participated in the study. More than 90% of the participants were having a positive attitude regarding the role of research enriching medical education and that it promotes critical thinking. The majority of them believed that research is also helpful for securing a better academic position. More than 90% agreed that research should be included in the MBBS/BDS curriculum. The major obstacles reported were lack of adequate funding (72.3%), lack of well-equipped laboratory (65.1%), non-inclusion of research as a subject in the medical curriculum (62.7%). Conclusions: The majority of participants were positive towards research. The major obstacles faced by medical professionals were lack of adequate funding, non-inclusion of research as a subject in the medical curriculum, lack of a well-equipped laboratory, lack of mentorship and incentives.